(untitled) (Aporia, 2017)
Free will and moral responsibility share an intricate relationship. Whether we deem an agent morally praiseworthy or morally blameworthy depends, in part, on whether or not the act was “performed freely”. However, numerous difficulties emerge when one tries to articulate what “performed freely” entails: one must not only provide an account of free will with reference to its nature, he or she must also take into consideration its compatibility, or lack thereof, with existing and/or potential features of the world. Ultimately, this paper attempts to do just that, to provide an account of free will that is both coherent and naturalistic. Consequently, I argue that such an account be contrived under the umbrella of agent-causal libertarianism using the mechanics of quiescence.